Mechanisms of esophageal cancer metastasis and treatment progress - Wang, Yusheng; Yang, Wei; Wang, Qianyun; Zhou, Yong (Frontiers in Immunology, 2023)
Esophageal cancer is a prevalent tumor of the digestive tract worldwide. The detection rate of early-stage esophageal cancer is very low, and most patients are diagnosed with metastasis. Metastasis of esophageal cancer mainly includes direct diffusion metastasis, hematogenous metastasis, and lymphatic metastasis. This article reviews the metabolic process of esophageal cancer metastasis and the mechanisms by which M2 macrophages, CAF, regulatory T cells, and their released cytokines, including chemokines, interleukins, and growth factors, form an immune barrier to the anti-tumor immune response mediated by CD8+ T cells, impeding their ability to kill tumor cells during tumor immune escape. The effect of Ferroptosis on the metastasis of esophageal cancer is briefly mentioned. Moreover, the paper also summarizes common drugs and research directions in chemotherapy, immunotherapy, and targeted therapy for advanced metastatic esophageal cancer. This review aims to serve as a foundation for further investigations into the mechanism and management of esophageal cancer metastasis.